THE SYNTHESIS OF BOARD GAME DESIGN FOR LEARNING ENHANCEMENT - Jaidee, Arnon; Jirasatjanukul , Kanokrat; Dokkularb, Prueksa (Journal of Graduate School Sakon Nakhon Rajabhat University, 2026)
This study aimed to (1) synthesize design guidelines for educational board games and (2) evaluate the synthesized guidelines for board game design to support learning. Data were collected from popular board games featured on the website inkru.com between 2022 and 2024, as well as research publications from 2021 to 2024. The study analyzed and synthesized formats, rules, and design conditions, after which five purposively selected experts evaluated the synthesized outcomes for appropriateness. The findings revealed that board games possess significant potential for enhancing critical thinking, problem-solving, collaboration, and communication skills. A well-balanced design between playfulness and academic content increased learners’ motivation. Notable examples include the Keyboard Kingdom and The Four-Region Jumping Frog, which incorporate clear rules, grid-based movement, and competitive goals. Narrative-driven games such as Puzzles and Truth or Trick stimulate imagination and engagement, while non-competitive games like Unplugged Coding and Infectious Diseases focus on creative learning. The analysis suggested that the design of educational board games should prioritize clear and comprehensible rules, strategic use of resources, engaging design elements, and storytelling that aligns with specified content. The overall appropriateness of the synthesized design guidelines was rated at the highest level ( = 4.73, S.D. = 0.41). Furthermore, the study recommends educational board game design should foster social interaction and team-based problem-solving to develop transferable skills. Competitive elements, such as battles, should be contextually adapted to educational settings and integrated with simulated scenarios to promote deeper learning. In conclusion, board games represent a powerful tool for enhancing learning and cultivating 21st-century skills.